2019
DOI: 10.1177/1941874419830496
|View full text |Cite
|
Sign up to set email alerts
|

Rates and Trends of Endotracheal Intubation in Patients With Status Epilepticus

Abstract: Objective: Among patients with status epilepticus, we sought to determine the rate of endotracheal intubation, identify the physician specialties responsible for endotracheal intubation, and characterize the trend in use of endotracheal intubation over the last 20 years. Methods: We performed a cross-sectional study using data from 2 sources. First, we used inpatient claims between 2009 and 2015 from a nationally representative 5% sample of Medicare beneficiaries. Patients with status epilepticus were identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 27 publications
3
13
0
Order By: Relevance
“…Our findings, although exploratory in nature due to a relatively low sample size, are relevant because in recent work examining 124 studies from 22 airway registries worldwide, etomidate is one of the most frequently used induction agents, particularly by emergency medicine physicians who perform over 50 % of intubations for SE in the United States. [2] , [21] Though the use of etomidate specifically in the intubation of patients with SE is not known, routine use is plausible. Indeed, in our study, etomidate was the most used drug for induction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings, although exploratory in nature due to a relatively low sample size, are relevant because in recent work examining 124 studies from 22 airway registries worldwide, etomidate is one of the most frequently used induction agents, particularly by emergency medicine physicians who perform over 50 % of intubations for SE in the United States. [2] , [21] Though the use of etomidate specifically in the intubation of patients with SE is not known, routine use is plausible. Indeed, in our study, etomidate was the most used drug for induction.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately one in three patients with SE requires intubation, and the incidence of intubation during SE appears to be increasing over the past 25 years. [2] While there is high quality evidence supporting first and second line SE treatment, strong evidence guiding RSE treatment is lacking. [1] , [3] , [4] , [5] , [6] , [7] Similarly, guidance on optimal anesthetic induction medication selection during rapid sequence intubation (RSI) for RSE is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Refractory status epilepticus in a patient who presented with or has ongoing convulsive status epilepticus should prompt ICU admission and consideration for tracheal intubation for the induction of anaesthesia. A study from the USA showed that approximately one in three patients with status epilepticus require tracheal intubation, a proportion that has nearly doubled over the last 20 years [29]. Of note, in a follow-up paper from Kapur et al [26], tracheal intubation rates varied greatly between centres, even when adjusted for early vital signs and post-treatment neurological recovery [30].…”
Section: Icu Management: Refractory and Super-refractory Status Epile...mentioning
confidence: 99%
“…26,27 Without an end point that includes EEG monitoring, patients intubated for neuroimaging or progression of a structural brain injury have been considered to have failed status epilepticus therapy regardless of the reason for intubation, a major limitation given that the rate of intubation has nearly doubled over the past 2 decades. 31 In critical care studies of status epilepticus utilizing continuous EEG, an aggressive approach to anesthetic weaning has demonstrated EEG normalization and clinical improvement despite initial increases in periodic discharges. 32 Although the literature suggests that metabolic crisis is associated with these high-frequency periodic discharges, 33 the emergence of ictal-interictal continuum activity may be transient in the setting of weaning from anesthetic coma.…”
Section: Eeg Neuromonitoring To Guide Liberation From Anesthetic Coma...mentioning
confidence: 99%
“…Rapid EEG has not been used to date in interventional clinical trials in the emergency department; thus, primary end points in acute status epilepticus clinical effectiveness trials have been limited to absence of clinically apparent seizures with improved consciousness and without additional antiseizure medication 26,27 . Without an end point that includes EEG monitoring, patients intubated for neuroimaging or progression of a structural brain injury have been considered to have failed status epilepticus therapy regardless of the reason for intubation, a major limitation given that the rate of intubation has nearly doubled over the past 2 decades 31 …”
Section: Eeg Neuromonitoring To Guide Liberation From Anesthetic Coma...mentioning
confidence: 99%